2000
DOI: 10.1074/jbc.m000030200
|View full text |Cite
|
Sign up to set email alerts
|

TASK-3, a Novel Tandem Pore Domain Acid-sensitive K+Channel

Abstract: Tandem pore domain acid-sensitive K ؉ channel 3 (TASK-3) is a new member of the tandem pore domain potassium channel family. A cDNA encoding a 365-amino acid polypeptide with four putative transmembrane segments and two pore regions was isolated from guinea pig brain. An orthologous sequence was cloned from a human genomic library. Although TASK-3 is 62% identical to TASK-1, the cytosolic C-terminal sequence is only weakly conserved. Analysis of the gene structure identified an intron within the conserved GYG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
298
3
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(321 citation statements)
references
References 30 publications
11
298
3
5
Order By: Relevance
“…Mammalian TASK-1 and TASK-3 form a subfamily of two-pore K ϩ channels that are activated by high pH, volatile anesthetics, and neurotransmitters (Duprat et al, 1997;Leonoudakis et al, 1998;Patel et al, 1999;Kim et al, 2000;Millar et al, 2000;Rajan et al, 2000;Talley et al, 2000). Our findings indicate that UNC-93 and SUP-10 associate with a SUP-9 two-pore K ϩ channel and suggest that UNC-93 and SUP-10 may be regulatory subunits of this channel.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Mammalian TASK-1 and TASK-3 form a subfamily of two-pore K ϩ channels that are activated by high pH, volatile anesthetics, and neurotransmitters (Duprat et al, 1997;Leonoudakis et al, 1998;Patel et al, 1999;Kim et al, 2000;Millar et al, 2000;Rajan et al, 2000;Talley et al, 2000). Our findings indicate that UNC-93 and SUP-10 associate with a SUP-9 two-pore K ϩ channel and suggest that UNC-93 and SUP-10 may be regulatory subunits of this channel.…”
Section: Introductionmentioning
confidence: 70%
“…SUP-9 is 49 -51% identical in amino acid sequence to human TASK-1(KCNK3), TASK-3(KCNK9), and TASK-5(KCNK15) channels as well as to two predicted Drosophila proteins. Mammalian TASK-1 and TASK-3 behave as pH-sensitive background K ϩ channels when expressed heterologously in mammalian cell lines (Duprat et al, 1997;Kim et al, 1998;Leonoudakis et al, 1998;Rajan et al, 2000), whereas the properties of TASK-5 channels remain unknown. All other identified human two-pore K ϩ channels, such as TREK-1(KCNK2), share Ͻ30% amino acid identity with SUP-9.…”
Section: Resultsmentioning
confidence: 99%
“…TASK-5 has been placed into the category of acid-sensitive channels based on its sequence homology to TASK-1 and 3. In cerebellar granule cells (Millar et al, 2000) and cranial motoneurons (Talley et al, 2000) receptor-mediated inhibition of TASK-1 has been reported and TASK-3 is activated by depolarization and modulated by extracellular divalent cations (Rajan et al, 2000). TASK-5 might then be similarly sensitive to activity and neuromodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the complexity of KCNK3 regulation, the closely related acid‐sensitive KCNK9 channel dimerizes with KCNK3, forming KCNK9‐KCNK3 heterodimeric channels in tissues where both channels are expressed 11, 12, 13, 14, 15. KCNK9 is more maximally activated at pH 7.4 than KCNK3 16, 17. The channels are co‐expressed in a variety of tissues, promoting tissue‐specific diversity of channel function.…”
Section: Introductionmentioning
confidence: 99%